Anxiety Levels among Primigravida Pregnant Women at the Menteng Public Health Center, Palangka Raya - Nur’aini, N.; Miden, Destinady K.; Sukriani, Wahidah (CV. Social Politic Genius (SIGn), 2024)
Anxiety among third-trimester primigravida is a significant public health issue that increases the risk of delivery complications, as well as maternal and infant morbidity and mortality. This study aimed to determine anxiety levels among primigravida based on age, education, occupation, income, and family support in the working area of the Menteng Primary Health Center (PHC) in Palangka Raya City. This quantitative study, with a descriptive cross-sectional design, involved 55 respondents selected through purposive sampling. Primary data were collected using the Perinatal Anxiety Screening Scale (PASS) questionnaire and a Likert-scale questionnaire for the family support variable, which were subsequently analyzed using univariate frequency distributions and percentages. The results showed that the majority of respondents experienced moderate anxiety (63.64%) and severe anxiety (18.18%). Moderate anxiety was predominantly experienced by the ideal reproductive age group of 20–35 years (62.50%), those with secondary education (63.89%), and the unemployed (housewives) (59.38%). Specifically regarding socio-economic indicators, moderate anxiety remained dominant among those with a husband’s income below the Regional Minimum Wage (RMW) (64.10%). Notably, the group receiving good family support (73.80%) contributed the highest rate of moderate anxiety. These empirical facts demonstrate that age maturity, financial stability, and family support do not automatically eliminate maternal anxiety approaching the first childbirth. Therefore, it is recommended that the PHC integrate psychological screening instruments into routine Antenatal Care (ANC) service standards to reduce the risk of complications at an early stage.